1977
DOI: 10.1002/aja.1001500111
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy of the developing alimentary canal in the chick

Abstract: Fresh pullet eggs (White Leghorn strain) were incubated from 11 to 21 days. Embryos were killed by decapitation and portions of the esophagus, crop, proventriculus, gizzard, small intestine, caecum and rectum were dissected and removed rapidly. The inner lining of the gut was exposed by using small needles to pin the cut edges of the tube to a wax plate immersed in Hank's fixative modified with aldehydes (Litke and Low, '77). Preparation for scanning electron microscopy (SEM) was routine.Esophageal cilia appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…In chick, ciliated cells first appear in the lower esophagus of the 13 day embryo (Ivey and Edgar, 1952). Using SEM, Lim and Low (1977) observed that ciliated cells were more profusely distributed at the lower end of the chick esophagus, in accordance with the observations of Ivey and Edgar (1952). In mouse, very few ciliated cells are seen at 15 days of gestation, but they are present in all regions of the esophagus.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In chick, ciliated cells first appear in the lower esophagus of the 13 day embryo (Ivey and Edgar, 1952). Using SEM, Lim and Low (1977) observed that ciliated cells were more profusely distributed at the lower end of the chick esophagus, in accordance with the observations of Ivey and Edgar (1952). In mouse, very few ciliated cells are seen at 15 days of gestation, but they are present in all regions of the esophagus.…”
Section: Discussionsupporting
confidence: 81%
“…In the chick, ciliation of the esophageal epithelium has also been reported (Ivey and Edgar, 1952;Van Alten and Fennell, 1957;Lim and Low, 1977). The presence of ciliated cells in the fetal mouse esophageal epithelium is reported here for the first time.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The developing longitudinal folds of the lamprey anterior intestine most closely resemble the previllous ridges in the developing avian duodenum (Tsai and Overton 1976;Lim and Low 1977) in that both follow a zigzag course. The primary difference is that in lampreys the pattern is irregular and more widely spaced such that the concavities and convexities of adjacent folds do not always meet as they do in the duodenum of a 15-day-old chick embryo (Lim and Low 1977).…”
Section: Discussionmentioning
confidence: 95%
“…The end of the rough endoplasmic reticulum is continuous to the smooth elements (arrows) on day E17. x 15,000 chick duodenum (COULOMBRE and COULOMBRE, 1958;GREY, 1972;BURGESS, 1975;LIM and Low, 1977) and the rat duodenum (KAMMERAAD, 1942;MATHAN et al, 1976;NAKAMURA and KoMURO, 1983). In the chick, the authors agreed in that villous primordia started as parallel previllous ridges, which folded to a regular zigzag pattern and then separated into individual villi, and these events proceeded synchronously throughout the mucosa.…”
Section: Distribution Of Proliferative Cells In Developing Villi and mentioning
confidence: 99%